2020
DOI: 10.21923/jesd.683679
|View full text |Cite
|
Sign up to set email alerts
|

Kocaeli̇ / Başi̇skele İlçesi̇ Afet Ve Aci̇l Durum Toplanma Alanlarinin Yeterli̇kleri̇ni̇n Değerlendi̇ri̇lmesi̇

Abstract: Doğal ya da insan kaynaklı tehlikelerin afete dönüşmemesi, koruyucu ve önleyici önlemlerin alınması ve risk azaltma faaliyetlerinin yürütülmesi ile mümkündür. Afetler sırası ve sonrasında kullanılmak üzere belirlenecek toplanma alanlarının kişi başına düşen alan açısından büyüklüğü, dağılım ve altyapı gibi özelliklerinin değerlendirilerek belirlenmesi afet yönetiminin en önemli konularından biridir. Bu çalışmada, Afet ve Acil Durum Yönetim Başkanlığı (AFAD) İl Müdürlükleri tarafından mahalle ve bölge düzeyinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
0
0
1
Order By: Relevance
“…As a result of these evaluations, it was determined that the existing emergency meeting areas of Kocaeli province's Başiskele district were appropriate. However, because the urban settlement was expected to increase over time, it was suggested that new assembly areas be created [21]. Using decision-making methodologies, Gökgöz et al (2020) evaluated the characteristics of emergency assembly areas.…”
Section: Studies On Emergency Assembly Areas In Turkeymentioning
confidence: 99%
“…As a result of these evaluations, it was determined that the existing emergency meeting areas of Kocaeli province's Başiskele district were appropriate. However, because the urban settlement was expected to increase over time, it was suggested that new assembly areas be created [21]. Using decision-making methodologies, Gökgöz et al (2020) evaluated the characteristics of emergency assembly areas.…”
Section: Studies On Emergency Assembly Areas In Turkeymentioning
confidence: 99%
“…Türkiye sahip olduğu meteorolojik, jeolojik ve topoğrafik koşullar sebebiyle sık sık afetlere maruz kalmaktadır (Kılcı vd., 2015;Kınay vd., 2018;Gerdan ve Şen, 2020). Doğal afetlerin verdiği zarar düşünüldüğünde, etki alanı ve yıkım gücü en yüksek olan depremdir (Xu vd., 2016;Şahin ve Hazırcı, 2019).…”
Section: Introductionunclassified